Transatmospheric ileal stoma manometry can be applied for the early detection of stoma outlet obstruction - Wang, Xiaowei; Wang, Yizhi; Lin, Beibei; Liu, Yue; Gu, Jin; Ling, Limian; Xu, Dong; Ding, Kefeng (Frontiers in Oncology, 2023)
Background Stoma outlet obstruction (SOO) is a common complication of diverting ileostomy and usually detected at the advanced stage when the intestine is obviously obstructed. The objective of this study is to explore the efficacy of transatmospheric ileal stoma manometry (TISM) in early detection of SOO before the manifestation of intestinal obstruction. Methods A single-center prospective study was performed in patients scheduled to undergo reversal ileostomy and laparoscopic anterior rectal resection and diverting ileostomy in Second Affiliated Hospital of Zhejiang University School of Medicine from 1st July 2022 to 31st December 2022. The stoma pressure was measured by TISM at different time points. Results The mean stoma pressure of the 30 patients before reversal ileostomy was 5.21 cmH2O which was considered as normal standard of stoma pressure, and ranged from 1.2 to 8.56 cmH2O. After excluding two patients with anastomotic leakage, a total of 38 patients who were subjected to laparoscopic anterior rectal resection and diverting ileostomy were further included in this study. The incidence of anastomotic leakage was 5% and that of SOO was 12.5%. The mean postoperative obstruction time was 5.2 (3-7) days and the mean time from elevated stoma pressure to diagnosed as SOO was 2.8 (2-4) days in the five patients who developed SOO. The pressure measured at the third stoma manometry time point (second day after return of gut function) (10.23 vs. 6.04 cmH2O, p<0.001) and the postoperative hospital stay (10 vs. 8.49 days, p=0.028) showed significantly difference between the SOO and non-SOO groups. The pressures measured at the first time point (before return of gut function) (4 vs. 4.49 cmH2O, p=0.585), the second time point (the day of return of gut function) (6.8 vs. 5.62 cmH2O, p=0.123), and the fourth time point (discharge day) (5.88 vs. 5.9 cmH2O, p=0.933) showed no significant difference in both groups. Conclusion TISM can be utilized for early detection of SOO and can be incorporated as a novel diagnostic method together with abdominal CT scan to realize the goal of ERAS.